Inkompatibilitas Metode Omnibus Law Dalam Penyederhanaan Regulasi - Idul Rishan; Imroatun Nika (Fakultas Hukum Universitas Islam Indonesia, 2022)
This study focuses on the application of the omnibus law method in the simplification of regulations. This study aims to analyze two things. First, the application of the omnibus law method in the simplification of regulations in Indonesia. Second, formulating the reasons from which the omnibus method is not compatible in the simplification of regulations. The method used is a doctrinal legal research based on secondary data. The results of the study conclude that: (1) there are 11 regulatory clusters in the Job Creation Law with 81 affected laws and 2 repealed laws. By the time this study was completed, the omnibus law method had produced 47 Government Regulations and 4 Presidential Regulations. (2) there is no correlation between the usefulness of the omnibus law method and the efforts to simplify regulations. There are three reasons behind it, which includes: (a) the absence of regulatory normality threshold indicators (b) the omnibus method is more compatible to be used as a technique for simplifying regulations and (c) the omnibus law method creates the need for complex regulatory synchronization and has the potential to increase the volume of regulation.Key Words: Omnibus law; simplification of regulations; job creationAbstrakStudi ini difokuskan pada penerapan metode omnibus law dalam penyederhanaan regulasi. Penelitian ini bertujuan untuk menganalisis dua hal. Pertama, penerapan metode omnibus law dalam penyederhanaan regulasi di Indonesia. Kedua, merumuskan alasan bahwa metode omnibus tidak kompatibel dalam menyederhanakan regulasi. Metode penelitian ini merupakan penelitian hukum doktriner dengan basis data sekunder. Hasil penelitian menyimpulkan: (1) terdapat 11 klaster pengaturan dalam UU CK dengan 81 undang-undang terdampak dan 2 undang-undang yang dicabut. Sampai dengan studi ini diselesaikan, metode omnibus law telah melahirkan 47 PP dan 4 Perpres. (2) tidak ada korelasi antara kegunaan metode omnibus dengan upaya penyederhanaan regulasi. Tiga alasan yang melatarbelakangi antara lain: (a) ketiadaan indikator ambang batas kenormalan regulasi (b) metode omnibus lebih kompatibel digunakan sebagai teknik penyederhanaan legislasi dan (c) metode omnibus law melahirkan kebutuhan sinkronisasi regulasi yang kompleks dan potensial menambah volume regulasi.Kata-kata Kunci: Omnibus law; penyederhanaan regulasi; cipta kerja